(untitled) (Global Journal of Management and Business Research, 2021)
The county government’s auditors have been experiencing the existence unreliable information systems, Lack of capacity to handle the financial complexities, Economic viability of some county governments in doubt, Political interference of in the process of procurement and staffing, weak governance structures for financial controls and reporting. All this has affected the financial accountability of internal audit services. Public finance accountability is increasingly becoming important in the public sector. One means of effecting accountability is through auditing. Despite the characteristics of auditor’s fraudulent activities, in efficiency and waste of public resources are increasingly high. This is a sad state of affairs as the county governments strive to become a middle income economy by 2030.